PRR1, a Homolog of Aspergillus nidulans palF, Controls pH-Dependent Gene Expression and Filamentation in Candida albicans - Porta, Amalia (American Society for Microbiology, 1999)
The pH of the environment has been implicated in controlling the yeast-hypha transition and pathogenesis of Candida albicans. Several C. albicans genes, including PHR1 and PHR2, are pH dependent in their expression. To investigate the mechanism of pH-dependent expression, we have cloned and characterized PRR1 (for pH response regulator). PRR1 is homologous to palF, a component of the pH response pathway in Aspergillus nidulans. Expression of PRR1 was itself pH dependent, being maximal at acid pH but reduced severalfold at alkaline pH. In a prr1 null mutant the alkaline-induced expression of PHR1 was completely abolished. Conversely, expression of PHR2 was no longer repressed at alkaline pH. A prr1 null mutant exhibited no morphological abnormalities at either pH; however, it lost the ability to form hyphae on medium 199 and on 10% serum plates. The ability to filament on serum was not restored by forced expression of PHR1, indicating that additional PRR1-dependent genes are required for hyphal development. These developmental genes appear to be distinct from those controlled by the developmental regulator EFG1, since the EFG1-dependent gene HWP1 was expressed normally in the prr1 null mutant. We conclude that PRR1 encodes a component of the pH-dependent response pathway in C. albicans and that this pathway regulates the expression of multiple components of hyphal development.